Numerical modelling of micro-plasto-hydrodynamic lubrication in plane strip drawing. (June 2017) - Carretta, Y.; Bech, J.; Legrand, N.; Laugier, M.; Ponthot, J.-P.; Boman, R.
Abstract: This paper presents a new finite element model capable of predicting the onset of micro-plasto-hydrodynamic (MPH) lubrication and the amount of lubricant escaping from surface pockets in metal forming. The present approach is divided in two steps. First, a simulation at the macroscopic level is conducted. Then, a second simulation highlighting microscopic liquid lubrication mechanisms is achieved using boundary conditions provided by the first model. These fluid-structure interaction computations are made possible through the use of the Arbitrary Lagrangian Eulerian (ALE) formalism. The developed methodology is validated by comparison to experimental measurements conducted in plane strip drawing. The effect of physical parameters like the drawing speed, the die angle and the strip thickness reduction is investigated. The numerical results show good agreement with experiments. Highlights: A multi-scale finite element model capable of modeling MicroPlastoHydrodynamic lubrication in plane strip drawing is set up. The interaction between a cavity filled with lubricant and the strip deformation are accounted for in the same model. Microscopic lubricant flow on the downstream and upstream the lubricant cavity are handled by using an ALE framework. The model accounts for the closure of the lubricant cavity when the hydrostatic pressure drops due to the leak of lubricant. Numerical results exhibits the same trends as experimental measurements.